2005
DOI: 10.7202/706233ar
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of Pratylenchus penetrans on various rotation crops in Quebec

Abstract: La reproduction du nématode des lésions racinaires Pratylenchus penetrans a été évaluée en serre sur 12 cultures de rotation. La moutarde brune (Brassica juncea) a été la meilleure plante hôte et a augmenté de 17,2 fois la population initiale. Le soja (Glycine max), le millet japonais (Echinochloa frumentacea), le colza (B. napus), le sarrasin (Fagopyrum esculentum), la moutarde blanche (B. hirta), et le raygrass vivace (Lolium perenne) ont été également très efficaces à multiplier le nématode et n'étaient pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 6 publications
3
34
1
2
Order By: Relevance
“…Traditionally, rye has been used by Quebec potato growers as a rotation crop. Rye was previously recognized to be a good host for P. penetrans (Bélair et al 2002;Dunn and Mai 1973;Olthof 1980;Thies et al 1995). Our results demonstrated that rotation with rye increased P. penetrans population densities in soil and, in addition, reduced potato yields.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Traditionally, rye has been used by Quebec potato growers as a rotation crop. Rye was previously recognized to be a good host for P. penetrans (Bélair et al 2002;Dunn and Mai 1973;Olthof 1980;Thies et al 1995). Our results demonstrated that rotation with rye increased P. penetrans population densities in soil and, in addition, reduced potato yields.…”
Section: Resultssupporting
confidence: 52%
“…Many studies have shown that pearl millet hybrids are poor hosts of P. penetrans under greenhouse and field conditions (Ball-Coelho et al 2003;Bélair et al 2002Bélair et al , 2005Jagdale et al 2000). However, some studies have shown that grain hybrids were less effective than CFPM 101 (a forage hybrid commonly used by growers) in reducing P. penetrans populations and improving potato yields (Ball-Coelho et al 2003;Bélair et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different species of weeds have been recognized as host plants for Pratylenchus spp. in diverse regions of the world, contributing to an increase of nematode populations in the soil, thus constraining the establishment of agricultural cultures (Kutywayo and Been, 2006;Bélair et al, 2007;Smiley et al, 2014). In this context, this work aimed to assess the reproductive capacity of P. zeae in different species of weeds.…”
Section: Introductionmentioning
confidence: 99%
“…Br.) is also a relatively poor host for root-lesion nematodes (Bélair et al 2002;Kimpinski and Kunelius 2001).…”
Section: Introductionmentioning
confidence: 99%